التنظيم القانوني لاستخدام تقنية الاتصال عن بعد في الإجراءات الجزائية من منظور القانون الإماراتي - Yacoup Mustafa Mahmoud Saleh; Wan Abdul Fattah Wan Ismail; Muzaffar Syah Mallow; Syahirah Abdul Shukor (Usuli Faqih Research Centre PLT, 2024)
Vol 10 No 1 (2021): Perdana: April Issue